Durability of Capital Goods: Taxes and Market Structure - Raviv, Artur; Zemel, Eitan (Econometrica, 1977)
This paper examines the durability of capital goods produced under different market structures when tax considerations are included. Since investment tax credit and depreciation allowances are realized by the owner of the durable good, the durability of products produced by an industry which sells its output differs from that of an industry which rents. For each of these two commercial forms we consider both monopolistic and competitive market structure. Potential gains from different forms of regulation are discussed.